High mass-loading and binder-free flexible vanadium-based oxide cathode for zinc-ion battery via a bridge of MXene. (20th April 2023) - Fang, Kan; Li, Fei; Wang, Gui-Gen; Liu, Yi-Lin; Tan, Man-Lin; Zhao, Da-Qiang; Zhang, Hua-Yu; Han, Jie-Cai
Highlights: High mass-loading (∼7 mg cm −2 ) and binder-free MCV@CC flexible cathode was fabricated through the hydrothermal process under the assistance of MXene bridge. The MXene bridge induces the growth of vanadium oxide on CC, achieving improved conductivity of the flexible electrode. The MCV@CC flexible cathode exhibits large areal capacity (2.36 mAh cm −2 ) and excellent cycling stability (capacity retention of 86.1% after 1200 cycles). Assembled quasi-solid-state MCV@CC//Zn flexible battery delivers potentially practical application in electronic products. Abstract: Flexible zinc-ion batteries (ZIBs) are promising power sources for portable devices due to their high safety and low production cost. However, the low mass-loading and limited areal capacity of cathode materials are the major problems blocking the practicability of ZIBs. Herein, a high mass-loading and binder-free flexible vanadium oxide (MCV@CC) cathode with a large areal capacity was fabricated via the bridge effect of MXene. The functional MXene bridge induces the growth of the vanadium oxide active layer on the carbon cloth (CC) flexible substrate. The binder-free cathode can reduce the electrochemically inactive weight of the whole electrode, which enhances the energy density of ZIBs. Consequently, the MCV@CC cathode (mass-loading of ∼7 mg cm −2 ) delivers a desirable areal capacity (2.36 mAh cm −2 ) and good cycling stability (capacity retention of 86.1% after 1200 cycles at 10 mA cm −2 ). Moreover, several ex-situ characterization results indicate that the reaction mechanism upon battery cycling is based on the reversible Zn 2+ /H + (de)intercalation in the vanadium oxide interlayer. Furthermore, the assembled quasi-solid-state MCV@CC//Zn flexible battery exhibits decent performance at different bending states. Such a bridge effect strategy sheds light on the construction of high mass-loading flexible electrodes for ZIBs applications.